Effect of organoclay and preparation method on properties of antimicrobial cellulose acetate films. Issue 6 (26th August 2018) - Rodríguez, Francisco J.; Abarca, Romina L.; Bruna, Julio E.; Moya, Paula E.; Galotto, María J.; Guarda, Abel; Padula, Marisa
Abstract : The aim of the present study was oriented to evaluate the effect of a commercial organoclay and the technique of preparation on the physical and antimicrobial properties of active eco‐friendly nanocomposites films. To this antimicrobial nanocomposite films were fabricated from cellulose acetate (CA) powder, triethyl citrate (TEC) plasticizer, a commercial organoclay Cloisite30B (C30B), and cinnamaldehyde (Ci) as active agent. All nanocomposites showed the intercalation of the polysaccharide inside the organoclay structure, however, the level of the intercalation and the quality of the clay dispersion were dependent on the method selected to prepare them (solution‐casting or extrusion). In addition, nanocomposites obtained by extrusion evidenced a better dispersion of organoclay. Important changes on the color properties of films were evidenced, which was associated to the thermal degradation of the quaternary ammonium surfactant of the Cloisite30B. On the other hand, organoclay was unable to reduce the cinnamaldehyde loss during the extrusion and storage, nevertheless, a slight effect of the Cloisite30B on the cinnamaldehyde release to a food simulant was observed to nanocomposites prepared by extrusion. Finally, despite cinnamaldehyde loss was observed over time, the content of residual active compound into the films was able to impart antimicrobial activity against Escherichia coli for 14 weeks. POLYM. COMPOS., 40:2311–2319, 2019. © 2018 Society of Plastics Engineers